Un arte mágico de evocación: La música nueva según Manuel de Falla - Cascudo García-Villaraco, Teresa (Brocar. Cuadernos de Investigación Histórica, 2013)
This article studies the definition of modern musical composition given by Manuel de Falla in his writings. It points out the importance of evocation, a term frequently used by the composer, and searches for its meaning in the context of the psycophysical aesthetics proposed by Émile Littré, Hyppolite Taine and Henri Bergson.